PERENCANAAN TITIK LAHAN PARKIR UMUM PADA KAWASAN KOMERSIAL JL. BOULEVARD DAN JL. PENGAYOMAN, KOTA MAKASSAR - Wahyuni, Arinda; Ahmad Nadhil Edar; Gusti Hardiyanti Musda (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Jl. Boulevard and Jl. Pengayoman is a commercial area in Makassar City. Jl. Boulevard and Jl. Protection is quite strategic because it can be reached by all levels of society from various means of transportation. Various community activities such as walking, jogging, shopping, office activities, etc. have resulted in the increase in parking for visitors' vehicles in the area, covering the shoulders of the road and pedestrians. From the results of our previous research, it is clear that the cause of illegal parking that occurs in the commercial areas of Jalan Boulevard and Jalan Pengayoman is the limited parking space in each commercial building and the standard for calculating parking spaces in the commercial areas of Jalan Boulevard and Jalan Pengayoman. This is what causes the loss of user comfort and the change in pedestrian function to illegal parking in the Jl. Boulevard and Jl. Pengayoman is therefore an action that is contrary to Islamic Sharia which is haram because it is illegal, does not comply with local legal regulations and also harms other people. So, to restore the comfort and function of pedestrians in the commercial area of Jl. Boulevard and Jl. Pengayoman, we will carry out further research with the title "Planning Public Parking Areas in Commercial Areas on Jalan Boulevard and Jalan Pengayoman in Makassar City", where this research is to solve the problem of lack of parking spaces so that there is no more illegal parking in commercial areas on Jalan Boulevard and Jalan Protection of Makassar City. Data analysis uses qualitative and quantitative analysis which is used to explain the results of survey interviews with users and observations carried out on Jl. Boulevard and Jl. Pengayomanof Makassar City with the results of a literature review regarding parking spaces. This research is expected to provide a real picture to researchers as academics and the government as policy makers regarding public facilities built for the common good, as study material to determine policies that might be implemented to improve or add to these public facilities, and as a source a reference for writers who might carry out studies on urban planning.